Calibration of Simulation for Soft Manipulators: A Case Study - Novaes, Luis C.; Matos, Victor S.; Mendes, J. V.; Santos, Marcella; Silva, Lucas C. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
This work proposes a guideline to calibrate a Finite Element Model (FEM) simulation of a soft manipulator. An overview of the fundamentals of this type of simulation and its usage in soft robotics is presented in a case study of the simulation of a prototype soft manipulator. The goal is to evaluate the accuracy of the position of the simulated model in comparison to a real soft manipulator. An examination of the relevant parameters in the simulation environment was performed, followed by a fine-tuning of these parameters to achieve an optimal result in terms of the fidelity of the simulation. The resulting method of calibration provided an average position error compare to the real model of 1.4 %, being suitable for similar manipulators.